Shrinking grasslands and means to combat fodder scarcity in the hilly region of the Nilgiris - Venkataramanan, R.; Sreekumar, C.; Raman, B. (Indian Farming, 2018)
Grasslands are not only an important source of fodder, but also very essential for their role in the ecosystem. The existing grasslands have to be conserved. Fodder management in hilly regions must be aimed at a continuous supply of green fodder throughout the year, for which there are plenty of options available.